Speaking anxiety among Saudi learners in English as a foreign language classroom - Al-Hnifat, Ma'in Ateyah
Speaking Anxiety (SA) is a complex phenomenon. A experienced by learners hinders their language learning and lead to problem such as being reluctant to participate in classroom activities and being overly dependent on their teacher. This study discusses the causes of English language speaking anxiety among Saudi university students and classroom practices to determine how to decrease SA from both learners' and teachers' perspectives. This descriptive case study employed mixed method: questionnaires, interviews and classroom observations. The data was generated throughout semester one of the academic years 20] 8/20] 9. The semester began in September 20] 8 and ended in January 2019. The questionnaire was completed by 180 undergraduate students aged between 19 and 21 following a compulsory, inten ive English course in preparatory year. The interview participants were 20 students and 12 English Foreign Language (EFL) teachers of the students. Eight classroom lessons were also observed. The qualitative data w re analyzed using thematic analysis, while the quantitative data were analyzed using descriptive statistical analysis. The finding revealed four main themes within the causes of SA: learners' attitudes and beliefs, teachers' behavior, cultural attitudes, and inappropriate classroom environment. The findings also revealed two main classroom practices that may reduce student' SA related to learner and teacher practice. It was also found that the majority of the instructors were not aware of SA and its possible debilitating influences on language learning, so they did not bear learners' SA in mind while they were training and teaching them. This study concludes that speaking anxiety among Saudi learners in EFL classroom is not only due to learner and teacher factors but also the deep-rooted culture of the country which expects learners to listen rather than verbally express themselves. To improve the EFL learning experience, teachers should take learners' SA into consideration, instead of ignoring it or leaving them to deal with it by themselves, and employ effective teaching strategies and classroom practices to reduc learners' SA.